DYNAMIC HEDGING UNDER TRANSACTION COSTS: A LITERATURE REVIEW - Yaghi, Maher (Assurances)

(untitled) (HEC Montréal, 2002)
This article presents an introduction to dynamic hedging with a description of the different methods already used to implement a discrete hedging program. Two very distinct approaches have been taken in the pursuit of dynamic hedging under transaction costs : Local in time and Global in time. In the first approach, the hedge timing strategy is fixed exogenously or the risk taken is fixed exogenously. The second approach proposes to achieve an element of optimality under the utility maximization approach. In the first section of the article, we will discuss the background into dynamic hedging. The second section will elaborate on the different methods that have been proposed so far and in the final section some concluding remarks are discussed.